Non-Traumatic Ileal Perforation: A Retrospective Study - Singh, Gurjit (Medknow Publications & Media Pvt Ltd, 2014)
OBJECTIVE: To determine clinical features, operative findings and post-operative complications in patients operated for non-traumatic ileal perforation and to discuss the role of typhoid vaccination. MATERIALS AND METHODS: A retrospective study was carried out from 2009-2010. Seven patients were admitted through casualty as cases of acute abdomen. Underlying conditions were typhoid ulcers (4 patients) and non-specific etiology (3 patients). Diagnosis was made on clinical grounds, laboratory investigations, radiology and operative findings. Exploratory laporotomy was done. Different variables studied post-operatively were wound infection, residual abscess, recurrence and delayed post-operative complications. RESULTS: Tenderness, distension and rigidity were found in maximum patients. Gases under diaphragm and air fluid levels were common radiological findings. However, widal test and blood culture for S. typhi was positive in four patients. Six patients had single perforation and one patient had two perforations, all being on antimesentric border of ileum. Maximum patients had peritoneal collection of less than 1000 ml. In five patients simple closure of perforation was done and in remaining two resection with end to side ileotransverse anatomosis was required. Wound infection and residual intraabdominal abscess were found in one patient each. CONCLUSION: Management criteria remain same in typhoid and non-specific perforations. Commonest cause of ileal perforation is typhoid fever in our country, so immunization against typhoid beyond 18 years of age is recommended.